PANDANGAN IBN QUDAMAH TENTANG WAKAF DAN RELEVANSINYA DENGAN WAKAF DI INDONESIA - Al-Asy’ari, M.Khoirul Hadi (Institut Agama Islam Negeri Kendari, 2016)
Abtract This research is based on a research library, which is based on the study of literature, this research theme is taken is endowment in view of Ibn Qudamah and its relevance to the development of waqf in Indonesia, in this paper, there are three important questions first, how the concept of waqf in Ibn Qudamah view, and secondly how sosiohistoris biography of Ibn Qudama? and thirdly how the relevance of the opinion of Ibn Qudama of endowments with the development of waqf in Indonesia?, with the approach of content analysis and historical for mencoa analyze endowments and life history of Ibn Qudama, the results of the research paper is first, knowing the concept of waqf Ibn Qudamah, and the second knowing Ibn Qudamah biography, and relevance of thought waqf Ibn Qudamah with developments in Indonesia. Keywords: Ibn Qudamah, waqf, and relevance.